New Technologies and Specialist Competencies in the Complex Study of Digital Images of a Person’s Appearance - V. A. Gazizov; I. N. Podvolotskiy (Теория и практика судебной экспертизы)
To improve the methods of portrait identification, the authors have analyzed the current state of the examination technology, requirements for the means and methods of its conduct. They have also studied the particularities of specialists’ interaction in the field of digital image analysis. The need to supplement the methodology with biometric and intelligent technologies is specifically noted. The importance of including in the research procedure the techniques for analyzing the digital media of portrait information to identify both the characteristics of the media itself and the parameters of formation, storage, and changes in the information on it is highlighted. Attention is focused on the expansion of the complex of features of a person’s appearance used in portrait identification with dynamic features for the study of which it is necessary to use mathematical comparison techniques. It is revealed that the solution of problems related to the identification of a person in the future should be carried out by comparing the entire complex of signs of anatomical and accompanying characteristics of the elements of appearance. In addition to traditional “qualitative-descriptive” research methods, it is necessary to use objective analytical methods, biometric recognition, artificial intelligence and involve specialists from related expert fields to develop methods of rapid diagnosis of facts specific to the study of digital portraits.